Validity of MABESTA: A 3D Visualization-Based Interactive Learning Media for Junior High School Students - Mochammad Ricky Rifa'i; Wachju Subchan; Trapsilo Prihandono (Jurnal Penelitian Pembelajaran Fisika, 2026)
The development of information and communication technology encourages educational innovation, especially science learning in junior high schools which is still dominated by lecture methods and conventional media, which causes low student activity and learning outcomes in the material of the earth and the solar system. Interactive learning media "MABESTA" based on 3D visualization is proposed as a solution to this problem. The purpose of this study is to analyze the level of validity of interactive learning media "MABESTA" based on 3D visualization. The research method used is the development research method with the ASSURE model which includes 6 stages, namely analyzing students, setting goals, selecting methods, media, and materials, utilizing media and materials, asking for student participation, and evaluating and revising. The subjects of this research and development are validators and audiences. The objects of this study are grade VII students of SMP Islam Kunir and SMP Islam Tempeh. Data analysis techniques used are quantitative descriptive analysis and qualitative descriptive analysis. The results of the study indicate that interactive learning media "MABESTA" based on 3D visualization is suitable for use in learning solar system material based on the final results of expert validators of 92%, practitioners of 91%, and student response tests of 97%. This means that in terms of the suitability of the content, appearance, presentation, and language used, this media is very valid and very interesting, so that it can be used as a supporting media in understanding material about the earth and the solar system.